Separation of Alkali Metals - Tikhomirov I. A. Ivan Arsentyevich (2003, 2003)
A new gallam-exchange technique for separation of alkali metals was developed. The alkali metal separation factors were determined for the gallam-exchange systems LiGa-NaOH, LiGa-KOH, and KGa-NaOH. The effect of temperature and concentration of the exchanging phases on the separation factors were studied for the systems LiGa-NaOH and LiGa-KOH. Kinetic parameters of lithium, sodium, and potassium element exchanges were determined. The properties of gallam-exchange and amalgam-exchange systems were compared.